Ultrastructural examination of testicular tissues and evaluation of ZO-1 protein levels obtained from azoospermic cases - Altun, Ayşe; Ersoy Çanillio?lu, Yasemin; Ünsal, Evrim; Karabulut, Seda; Hürda?, Canan (Ondokuz Mayıs Üniversitesi, 2021)
Spermatogenesis is a process that involves cellular and biochemical processes. The purpose of this study is to understand the role of tight junctions in spermatogenesis by evaluating Zonula occludens-1 (ZO-1) protein levels of cells from the testicular sperm extraction (TESE) biopsies in patients with azoospermia. The study included 40 infertile men with azoospermia. They were divided into two groups, as spermatozoa positive (n=20) and spermatozoa negative (n=20). Testis tissues were examined morphologically, immunohistochemically and ultrastructurally by using transmission electron microscopy (TEM). The structure of seminiferous tubules was deteriorated, degenerated and hyalinized in spermatozoa negative group. ZO-1 expression level was normal in blood-testis barrier of spermatozoa positive group in comparing to lateral surfaces of Sertoli cells spermatozoa negative group. The ultrastructural results were also supported with light microscopy findings. These findings suggest that decrease of the ZO-1 protein expression level in Sertoli cells might be one of the factors involved in the impairment of spermatogenesis in spermatozoa negative group. Therefore, we suggest that tight junctions may have crucial roles in spermatogenesis.
Keywords: Azoospermia; Male Infertility; TESE; Tight Junction’s Protein ZO-1